IMPROVING RECOUNT TEXT WRITING ACHIEVEMENT OF THE EIGHTH GRADE STUDENTS OF SMP N 11 PALEMBANG THROUGH GENRE-BASED APPROACH (GBA) - Putri Purnama Sari; Zuraida Zuraida; Fiftinova Fiftinova (Faculty of Teacher Training and Education, Universitas Sriwijaya, 2015)
Abstract: The objectives of this study were to find out (1) whether or not there was any significant difference on recount text writing achievement between the eighth grade students of SMPN 11 Palembang who were taught through Genre-Based Approach (GBA) and those who were not, and (2) the aspects of writing that the students mostly improve after they were taught through Genre-Based Approach (GBA). In this study, the writer used quasi-experimental design. The population of this study was 357 eighth grade students of SMP N 11 Palembang in academic year 2013/2014. The sample of this study was 80 students taken from the population by using purposive sampling method in which 40 students belonged to VIII.2 and 40 students belonged to VIII.3. Class VIII.2 was the experimental group and VIII.3 was the control group. The results of the analysis by using independent sample t-test showed that there was significant difference on recount text writing achievement between the eighth grade students of SMPN 11 Palembang who were taught through GBA and those who were not taught through GBA (15.202 > 1.991, p < 0.05). Besides, the aspects of writing that the students mostly improve after they were taught through GBA was spelling and grammar aspect (77.91 > 35.41, mean difference = 42.49). Therefore, it is suggested for the English teachers to use GBA to teach recount writing. Key words: Genre-Based Approach (GBA), Improve, Recount Text, Writing